Facts about sex a basic guide Sol Gordon - Gordon, Sol 1923-; Cohen, Vivien (New York John Day, 1970)
Describes the process of sexual maturation in the adolescent, defines intercourse, and includes definitions of vulgar or slang terms used in reference to sex and sexual organs.
Previous ed. published under title: Facts about sex for exceptional youth. Rev. ed. published in 1973 under title: Facts about sex for today's youth.
Bibliography: p. 45-48.
Keywords: Sex instruction for youth; Sex instruction for youth